Pathological Osteoclasts and Precursor Macrophages in Inflammatory Arthritis - Hasegawa, Tetsuo; Ishii, Masaru (Frontiers in Immunology, 2022)
Macrophages comprise a variety of subsets with diverse biological activities, including inflammation, tissue repair, regeneration, and fibrosis. In the bone marrow, macrophages differentiate into multinucleated osteoclasts, which have a unique bone-destroying capacity and play key roles in physiological bone remodelling. In contrast, osteoclasts are also involved in pathological joint destruction in arthritis and it has been unclear whether the osteoclasts in different tissue settings arise from similar monocytoid precursors and share similar phenotypes. Rapid progresses in the next-generation sequencing technologies have provided many valuable insights regarding the heterogeneity of different types of osteoclasts. The application of single-cell RNA sequencing (scRNA-seq) to the defined osteoclast precursor-containing population enabled the identification of the specific subpopulation differentiating into pathological osteoclasts in joints. Furthermore, an intravital imaging system using two-photon microscopy has been applied to the synovial tissues to observe the real-time dynamics of immune cells in situ. These technologies together contributed to characterize the unique macrophages in the inflamed synovium, termed “arthritis-associated osteoclastogenic macrophages (AtoMs)”, causing the pathological bone erosion in inflammatory arthritis. Here, we review and discuss how novel technologies help to better understand the role of macrophages in inflammatory arthritis, especially focusing of osteoclastogenesis at the pannus-bone interface.